Classification of stressful factors associated with COVID-19 pandemic and quarantine among Ukrainian military personnel - Danilevska, N. V.; Данілевська, Наталя Володимирівна; Данилевская, Н. В. (Запорізький державний медичний університет, 2022)
The COVID-19 pandemic and quarantine have caused psychological distress, which has led to mental and physical health problems and changes in the behavior patterns of many people. It is known that the cause of such stress in the civilian population is not a pandemic or quarantine in general, but only some of their components. However, although COVID-19 pandemic and quarantine can provoke health disorders also in military personnel, stressful factors directly triggering these disorders have not yet been identified. Aim: to identify the immediate stressors that threaten Ukrainian military personnel health during the COVID-19 pandemic and quarantine. Materials and methods. The study was conducted at the Zaporizhzhia Military Hospital and Zaporizhzhia State Medical University between March 2020 and May 2020. A total of 25 military personnel hospitalized during this period were examined. Clinical, psychopathological, psychological examinations was conducted. The Fear of COVID-19 Scale was also used.

Пандемія COVID-19 і карантин стали для багатьох людей причиною психологічного дистресу, який спровокував порушення психічного, фізичного здоров’я та поведінкових патернів. Відомо, що причиною такого стресу в популяції цивільних людей є не пандемія та карантин загалом, а тільки окремі їхні компоненти. Незважаючи на те, що пандемія COVID-19 і карантин можуть провокувати погіршення здоров’я військовослужбовців також, стресогенні фактори, що безпосередньо викликали ці розлади у військовослужбовців, досі не встановлені. Мета роботи – виявити безпосередні стресові фактори, що є причиною погіршення стану здоров’я українських військовослужбовців під час пандемії COVID-19 і карантину. Матеріали та методи. Дослідження здійснили на базі Запорізького військового госпіталю та Запорізького державного медичного університету в період з березня до травня 2020 року. Обстежили військовослужбовців, які були госпіталізовані в цей період, – 25 осіб. Здійснили клінічне, клініко-психопатологічне, психодіагностичне дослідження. Під час дослідження використовували Шкалу страху COVID-19.

Пандемия COVID-19 и карантин стали для многих людей причиной психологического дистресса, который спровоцировал нарушение психического и физического здоровья и поведенческих паттернов. Известно, что причиной такого стресса в популяции гражданских лиц является не пандемия и карантин в целом, а лишь отдельные их компоненты. Несмотря на то, что пандемия COVID-19 и карантин также способны провоцировать ухудшение здоровья военнослужащих, стрессогенные факторы, которые непосредственно вызвали эти расстройства у военнослужащих, до сих пор не установлены. Цель работы – установить непосредственные стрессовые факторы, которые являются причиной ухудшения состояния здоровья украинских военнослужащих во время пандемии COVID-19 и карантина. Материалы и методы. Исследование проведено на базе Запорожского военного госпиталя и Запорожского государственного медицинского университета в период с марта по май 2020 года. Обследовали всех военнослужащих, которые были госпитализированы в этот период, – 25 лиц. Проведено клиническое, клинико-психопатологическое, психодиагностическое исследование. В ходе работы использовали Шкалу страха COVID-19.
Класифікація стресових факторів, пов’язаних із пандемією COVID-19 та карантином, серед військовослужбовців української армії
Классификация стрессовых факторов, связанных с пандемией COVID-19 и карантином, среди военнослужащих украинской армии
ORCID ID: 0000-0002-7854-9007
Keywords: stress; risk factors; COVID-19; pandemic; quarantine; health disorders; military; стрес; фактори ризику; пандемія; карантин; розлади здоров’я; військовослужбовці; стресс; факторы риска; пандемия; расстройства здоровья; военнослужащие